1973
DOI: 10.1139/o73-178
|View full text |Cite
|
Sign up to set email alerts
|

The Chemical Composition and Serological Reactions of Lipopolysaccharides from Serogroups A, B, X, and Y Neisseria meningitidis

Abstract: The chemical composition and serological reactions of lipopolysaccharides from serogroups A, B, X, and Y Neisseria meningitidis. Can. J. Biochem. 51, 1347Biochem. 51, -1354Biochem. 51, ( 1973.Analyses of the cell wall lipopolysaccharides prepared from Neisseria meningitidis serogroups A, B, X, and Y, indicated that they all contained glucose, galactose, glucosamine, heptose, lipid A, ethanolamine, fatty acids, phosphate, and protein. &me minor compositional differences in the sugar components did occur in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0
1

Year Published

1974
1974
1992
1992

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 9 publications
4
18
0
1
Order By: Relevance
“…Although the presence of sialic acid in meningococcal glycolipids has been reported by numerous investigators (19,23,27,28,41), it should be noted that the results of these and other studies (10,20,42,45,46,49,51,58) were derived from material cleaved under acidic conditions that could degrade possible constituents of LOS (e.g., sialic acid, fucose, and phosphate) (Fig. 6B).…”
Section: Resultsmentioning
confidence: 54%
“…Although the presence of sialic acid in meningococcal glycolipids has been reported by numerous investigators (19,23,27,28,41), it should be noted that the results of these and other studies (10,20,42,45,46,49,51,58) were derived from material cleaved under acidic conditions that could degrade possible constituents of LOS (e.g., sialic acid, fucose, and phosphate) (Fig. 6B).…”
Section: Resultsmentioning
confidence: 54%
“…Lipopolysaccharide (LPS) was visualised as the typical "smeared" appearance distal to this band. All meningococcal LPS, except that of group A strains, has been shown to consist of the same tetrasaccharide backbone bound to 2-keto-3-deoxyoctonate (KDO) (Jennings et al, 1973), making immunological cross-reactivity possible at this site. The structure of LPS of commensal Neisseria spp.…”
Section: Discussionmentioning
confidence: 99%
“…Preparation of lipid A from LPS. Lipid A was prepared as described by Jennings et al (4). About 60 mg of LPS was heated at 1000C with 5 ml of 0.1 N acetic acid for 2 h. The lipid precipitate was removed by centrifugation and washed with water, dissolved in chloroform, and reprecipitated in acetone (1 part lipid to 3 parts acetone).…”
Section: Methodsmentioning
confidence: 99%
“…Colonial types identified by Kellogg et al (8), of importance since it was shown that type 1 and 2 gonococci are virulent for humans whereas types 3 and 4 are not, are currently being investigated in regard to immunological and chemical differences. Perry et al (15) examined the LPS of type 1 and 4 gonococci and found that type 1 "smooth" preparations possessed characteristic sugars which were absent or different in concentration from those in "rough" type 4 LPS. Common to both were lipid A and a core fragment composed of n-glucose, Dgalactose, heptose, and 2-keto-3-deoxyoctulosonic acid (KDO).…”
mentioning
confidence: 99%